Influence of Outdoor Advertising on Direct Brand Contact of Customers in Abuja FCT - Mustapha, Safiya; Ogande, Anthony; Akpede, K. S. (EDUMALSYS Journal of Research in Education Management, 2025)
This study investigates the influence of outdoor advertising on customers’ direct brand contact in Abuja, Federal Capital Territory (FCT). The research objective is to determine the extent of exposure to outdoor advertising among customers and to assess which outdoor formats most strongly facilitate direct brand contact. A survey research design was employed with a population of 3,713,408 (NBS, 2022); simple random sampling was used across the area councils to select 400 respondents who completed a questionnaire. Data were collated and analyzed using simple frequency and percentage scores. Key findings indicate that customers are exposed to outdoor advertising and that billboard advertising generates more direct brand contact than other advertising forms in the FCT. The study concludes that outdoor advertising is effective in fostering direct brand contact. The contribution and implication of these findings are that advertisers should prioritize and increase investment in outdoor platforms, particularly billboards to enhance audience impact and strengthen brand–customer touchpoints in Abuja.